2019
DOI: 10.1109/access.2019.2952609
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Models for Early Stage Detection of Autism Spectrum Disorders

Abstract: Autism Spectrum Disorder (ASD) is a group of neurodevelopmental disabilities that are not curable but may be ameliorated by early interventions. We gathered early-detected ASD datasets relating to toddlers, children, adolescents and adults, and applied several feature transformation methods, including log, Z-score and sine functions to these datasets. Various classification techniques were then implemented with these transformed ASD datasets and assessed for their performance. We found SVM showed the best perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 31 publications
3
78
0
1
Order By: Relevance
“…To further explore the cross-cultural validity of the instrument we applied the three ML classi ers to the 10 items selected by Allison and colleagues on the Q-CHAT-10 (2012) [19] and we found that, in our sample, SVM algorithm was able to classify autism with 87% accuracy, 65% sensitivity and 86% speci city. These results are in line with those recently reported by Akter et al (2019) [29], where a dataset of Q-CHAT-10 administered using a mobile application [27] was analyzed using ML and the SVM algorithm was able to classify autism with 98% of accuracy. Together, these ndings con rm a satisfactory cross-cultural validity of the Q-CHAT in different samples, countries and languages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To further explore the cross-cultural validity of the instrument we applied the three ML classi ers to the 10 items selected by Allison and colleagues on the Q-CHAT-10 (2012) [19] and we found that, in our sample, SVM algorithm was able to classify autism with 87% accuracy, 65% sensitivity and 86% speci city. These results are in line with those recently reported by Akter et al (2019) [29], where a dataset of Q-CHAT-10 administered using a mobile application [27] was analyzed using ML and the SVM algorithm was able to classify autism with 98% of accuracy. Together, these ndings con rm a satisfactory cross-cultural validity of the Q-CHAT in different samples, countries and languages.…”
Section: Discussionsupporting
confidence: 91%
“…In the rst study, Thabath and colleagues (2019) [28], analyzed the adult version of the AQ-10 using a new rules-machine learning (RML) and were able to achieve an accuracy of about 90%, sensitivity of 87% and speci city of about 90%, while in the second study, the same authors applied the Naïve Bayes algorithm to the AQ-10 and found a similar accuracy of 92.8%, 91.3% and 95.7% for the child, adolescent and adult versions respectively. To the best of our knowledge, the only study applying ML to toddlers was conducted by Akter and colleagues (2019) [29], who analyzed the Q-CHAT-10 collected using the dataset from the ASDTests app and found that using a range of different classi ers, when optimized, they were able to effectively classify autism with an accuracy of 98%.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have applied machine learning techniques to examine whether the process of diagnosing ASD can be improved by statistically identifying reduced subsets of features from existing diagnostic instruments reaching from self-administered screening questionnaires to clinician-administered diagnostic tools (for a recent overview, see Thabtah 32 ). A few authors have shown that efficiency and accessibility of existing pre-diagnostic screening questionnaires such as the Autism-Spectrum Quotient (AQ) [33][34][35] or the Social Responsiveness Scale (SRS) 36,37 can be improved using machine learning. Similar machine learning experiments have been run to identify subsets of behavioral features from clinician-administered diagnostic tools, namely ADOS (Module 1 to 3) [38][39][40][41][42] and ADI-R 36,39,43 .…”
mentioning
confidence: 99%
“…In the voxel-based algorithms, Ecker et al performed ASD classification according to the local differences of voxel value in white matter and obtained 81% accuracy [17]. Uddin et al divided the original 3D MRI data into several small blocks, and analyzed the features of these small blocks.…”
Section: A Information Extraction Of Smrimentioning
confidence: 99%